Stability of luciferase plasmid entrapped in cationic bilayer vesicles - Manosroi A. (2014)
Characteristics and physical stability of luciferase plasmid (pLuc) entrapped in cationic bilayer vesicles prepared from various molar ratios of amphiphiles (DPPC, Tween61 or Span60), cholesterol (Chol) and cationic charge lipid (DDAB) were investigated. The cationic liposomes were composed of DPPC/Chol/DDAB in the molar ratio of 7:2:1. The cationic (Tween61 or Span60) niosomes were composed of Tween61/Chol/DDAB or Span60/Chol/DDAB in the molar ratio of 1:1:0.05. The maximum loading of pLuc was 15.29, 22.70, and 18.92 μg/mg of the total lipids or surfactants of liposomes, Tween61 and Span60 niosomes, respectively. The morphology of the vesicles showing multilamellar structure was characterized by transmission electron microscope (TEM). The particle sizes of the vesicles in nanosize range (160-850 nm) were determined by Photon Correlation Spectroscopy (PCS). Gel electrophoresis and gel documentation were modified to determine the entrapment efficiency of pLuc in cationic bilayer vesicles. The cationic bilayer vesicles gave the pLuc entrapment efficiency of 100%. The pLuc entrapped in cationic liposomes exhibited higher stability than pLuc in solution and pLuc entrapped in cationic Tween61 or Span60 niosomes, when stored at 4, 30 and 50 °C for 8 weeks. After 8 weeks at 4 °C, pLuc contents remained in cationic liposomes was 2 and 3 times higher than cationic Span60 and Tween61 niosomes, respectively. After 3 weeks, 50 and 2% of pLuc was remained in cationic liposomes at 30 and 50 °C respectively, whereas all pLuc in cationic Span 60 and Tween61 niosomes were degraded within 2 and 1 week, respectively. At 30 and 50 °C, pLuc in an aqueous solution or in bilayer vesicular formulations were not in a stable supercoil form. This study has indicated that the stability of pLuc can be enhanced by entrapping in cationic liposomes more than in niosomes. Higher temperature with increase storage time can affect the stability of pLuc even entrapped in bilayer vesicles. © 2008 Elsevier B.V. All rights reserved.